Nutritional Food Security in Peru: Agrifood Availability - Chagua Rodríguez, Perfecto (2019)
It is necessary to know the definition of Nutritional Food Security, under a right to food approach. FAO and national policies define it as: “Nutritional food security is the physical, economic and socio-cultural access of all people at all times to sufficient, safe and nutritious food, so that they can be used properly to meet their nutritional needs, in order to lead an active and healthy life”. This study presents the results of the descriptive analysis on Nutritional Food Security in Peru, focused on the analysis of the Agro-Food Availability component and its nutritional contribution towards the person.